Refleksja nad badaniami z zakresu pedagogiki medialnej prowadzonymi w Katedrze Pedagogiki Wczesnoszkolnej i Pedagogiki Mediów Uniwersytetu Śląskiego w Katowicach - Huk, Tomasz (Chowanna, 2019)
The paper characterizes the problem of research in the field of media pedagogy conducted in the team functioning in the Department of Early Childhood Education and Media Pedagogy at the University of Silesia in Katowice. Selected research areas conducted by individual members of the team are presented against the background of the development of media pedagogy in Poland. The research concerned sharenting, educational benefits achieved by students through the media, media education of parents, use of computers in pre-school education, persuasive messages or shaping competence in the field of information technology among the Masai on African land. The wide spectrum of analyses undertaken by the media pedagogy team is also the result of the team’s cooperation with various research centres in Poland and abroad.